2014
DOI: 10.1017/jns.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

In vitro disappearance characteristics of selected categories of commercially available dog treats

Abstract: Pet owners desire treats with adequate nutritional profiles, functional benefits, long-lasting properties and an interactive nature. Therefore, it is pivotal to understand the digestion characteristics of treats produced by different processing methods and having variable nutritional composition. The objective of the present study was to measure in vitro disappearance characteristics of selected categories of commercially available treats. In vitro procedures developed by Boisen and Eggum in 1991 were modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Dry matter disappearance of DE treats were highly variable in gastric phase, varying from 14.62% to 86.24% but were highly digestible at intestinal phase (>87%), except for DE5 that had a DMD of 62.01% ( Table 3 ). These findings are in accordance with our previous study ( de Godoy et al, 2014 ), which indicated that the use of wheat gluten may not lead to lower DMD because the variation in treat recipes and processing may result in different interactions among ingredients and in final product digestibility.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Dry matter disappearance of DE treats were highly variable in gastric phase, varying from 14.62% to 86.24% but were highly digestible at intestinal phase (>87%), except for DE5 that had a DMD of 62.01% ( Table 3 ). These findings are in accordance with our previous study ( de Godoy et al, 2014 ), which indicated that the use of wheat gluten may not lead to lower DMD because the variation in treat recipes and processing may result in different interactions among ingredients and in final product digestibility.…”
Section: Resultssupporting
confidence: 93%
“…Bones are the most common esophageal foreign bodies that have been reported in dogs ( Luthi and Neiger, 1998 ). In addition, bone category has been reported as the least digestible treat category in a previous study ( de Godoy et al, 2014 ). Chew treats, rawhide, and some dental chew treats have also been reported to cause severe obstruction within the esophagus of dogs ( Leib and Sartor, 2008 ).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Serum activities of CK and AST reflect damage of muscle and are useful markers to determine the condition of muscle tissue both in dogs [10, 13, 23, 24] and humans [25, 26]. In particular, increases in CK following physical activity has been associated with muscle damage in both racing and hunting dogs [9] and similar findings have been described in humans [8, 25].…”
Section: Discussionmentioning
confidence: 82%